use of an innovative device to improve the efficiency of the posterior quadriceps muscle of the man after the anterior cruciate ligament injury of advanced soccer players - Jawad Kadhim, Mohammed; Mousa, Abdulrahman (Journal of Physical Education, 2024)
Objective of the research This study aimed to manufacture an innovative device that enables the player to walk after the operation and improves functional efficiency through improvement in the range of motion as well as improvement in the size of the muscles working on the knee joint Imposing research There are statistically significant differences between the pre and posttests of the experimental and control groups, there are Statistically significant differences between the post-tests between the experimental group and the control group in favor of the experimental group of the research sample. The researchers used the experimental approach by designing the control and experimental groups with a test (pre-post) for the suitability of the approach to the research problem. The study population consisted of players with severed anterior cruciate ligaments for advanced soccer players, and the number of the research sample was (5) injured for the control sample and (5) for the experimental sample. The researchers concluded that the use of the innovative device showed good results in accelerating the rehabilitation process, and the development of body parts was In line with the progress of bending and stretching in the innovative device. There is no delay for one part of the body at the expense of another part, the most important recommendations. The necessity of using partial movement braces in the rehabilitation of the anterior cruciate ligament injury of the knee in advanced soccer players, the use of the number of walking steps and the pressure applied to the ground as a criterion for the progress of rehabilitation and recovery, the researcher recommends using the device early after the operation.